The public perception on the determinants of divorce : a case study in UiTM Kota Samarahan/ Kurnia Rahman & Nor Hani Matarol - Rahman, Kurnia; Matarol, Nor Hani (2018)
The divorcing is a common things that happened nowadays. The divorcing cases keep on increasing in every year. It gives a major concern toward the family institutions as it can give negative impacts to the divorce and the society. The divorcing cases in Malaysia happened due to few reasons or determinants. Thus, this study is to identify the determinants of divorce among the public. We have used a convenient sampling technique and 254 questionnaires has been distributed among the staff at UiTM Kota Samarahan, Sarawak.